Conceptual Logical Model of Managing the Development of Local Food Markets in the Context of Intermunicipal Socioeconomic Differentiation - KUZMINA, Natalia Leonidovna; TONYSHEVA, Lyubov Leonidovna (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018, 2018)
The article proposes the author's conceptual logical model of managing the development of local food markets in the context of intermunicipal socioeconomic differentiation, which reflects the course of strategic decision-making in order to achieve a spatial balance of supply and demand for food products, based on the interests of the agents of the regional reproduction cycle of food products. It allows substantiating a set of strategic measures to ensure sustainable development of the region. The algorithm of strategic management of the local food markets’ development in the region has been formed, which includes three consecutive stages. The principles aimed at ensuring a balance of supply and demand of food products in modern conditions have been defined. The necessity to regulate the local food market development in the region has been justified, based on the proposed managerial tools for the development strategizing.